2014
DOI: 10.3390/s141017981
|View full text |Cite
|
Sign up to set email alerts
|

Microelectronics-Based Biosensors Dedicated to the Detection of Neurotransmitters: A Review

Abstract: Dysregulation of neurotransmitters (NTs) in the human body are related to diseases such as Parkinson's and Alzheimer's. The mechanisms of several neurological disorders, such as epilepsy, have been linked to NTs. Because the number of diagnosed cases is increasing, the diagnosis and treatment of such diseases are important. To detect biomolecules including NTs, microtechnology, micro and nanoelectronics have become popular in the form of the miniaturization of medical and clinical devices. They offer high-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 110 publications
0
18
0
Order By: Relevance
“…Biosensors facilitate the study of memory, plasticity, and behavior or to monitor animal model conditions, the microelectrodes for fast‐scan cyclic voltammetry (FSCV) and electrophysiology to microdialysis probes for sampling and detecting various neurochemicals are generated (Castagnola et al, 2020). In addition, there are related electrochemical techniques (non‐biosensors) that have been useful in detecting, along with carbon fiber microelectrics, the release of transmitters such as DA (Mirzaei & Sawan, 2014). These methods offer excellent spatial resolution at a fast time.…”
Section: Resultsmentioning
confidence: 99%
“…Biosensors facilitate the study of memory, plasticity, and behavior or to monitor animal model conditions, the microelectrodes for fast‐scan cyclic voltammetry (FSCV) and electrophysiology to microdialysis probes for sampling and detecting various neurochemicals are generated (Castagnola et al, 2020). In addition, there are related electrochemical techniques (non‐biosensors) that have been useful in detecting, along with carbon fiber microelectrics, the release of transmitters such as DA (Mirzaei & Sawan, 2014). These methods offer excellent spatial resolution at a fast time.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reviews discussed sensors and sensing systems in all these domains from the points of view of their component blocks and subsequent technology, with a focus on the aspects that allowed miniaturisation and wearability. Extensive and very recent reviews can be found in [58], [61], [62], [63], [64], [59] and [65]. However, the resultant amount of data was not discussed so far in the literature.…”
Section: B Sensors: What Can They Offer the Human Machine Problemmentioning
confidence: 99%
“…Enzyme field effect transistors (ENFETs) are electronic devices that integrate in the same chip a FET (field effect transistor) with a sensitive enzymatic membrane for biorecognition purposes [ 1 ]. ENFET fabrication is a complex interdisciplinary technology related to microelectronics [ 2 ], biochemistry [ 3 ], nanomaterials for biostructures, and biocompatibility [ 4 ]. On the other hand, metal oxide semiconductor (MOS) downscaled technology has just reached its ultimate stage.…”
Section: Introductionmentioning
confidence: 99%